INDEPENDENT INDIA AND FREEDOM: A CRITICAL STUDY OF ARUNDHATI ROY’S “THE SILENCE IS THE LOUDEST SOUND” - Pravina, V. R. Raja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Arundhati Roy is a rebellious writer who has written about inequalities, hegemony, communal conflicts, globalization, economic imperialization and identity crisis in her novels and non-fiction. She is well known for her Booker Prize winning novel, The God of Small Things. Besides this success, she is also known for her non- fictional writings, in which she expresses her concern for human and environmental welfare. In 2020, she published nine essays as an essay collection. She titled the collection as Azadi: Freedom Fascism Fiction. In the collection she has reflected on the themes like freedom, fascism and fabrication of fiction as facts. This paper will explore the essay entitled, “The Silence Is the Loudest Sound”. The objective of the paper is to throw light on the kind of freedom, democracy and secularism prevailing in Jammu and Kashmir.